Basin‐scale fluid movement patterns revealed by veins: Wessex Basin, UK. Issue 1 (21st May 2015) - Worden, R. H.; Benshatwan, M. S.; Potts, G. J.; Elgarmadi, S. M.
Abstract: Calcite veins at outcrop in the Mesozoic, oil‐bearing Wessex Basin, UK, have been studied using field characterization, petrography, fluid inclusions and stable isotopes to help address the extent, timing and spatial and stratigraphic variability of basin‐scale fluid flow. The absence of quartz shows that veins formed at low temperature without an influence of hydrothermal fluids. Carbon isotopes suggest that the majority of vein calcite was derived locally from the host rock but up to one quarter of the carbon in the vein calcite came from CO2 from petroleum source rocks. Veins become progressively enriched in source‐rock‐derived CO2 from the outer margin towards the middle, indicating a growing influence of external CO2 . The carbon isotope data suggest large‐scale migration of substantial amounts of CO2 around the whole basin. Fluid inclusion salinity data and interpreted water‐δ 18 O data show that meteoric water penetrated deep into the western part of the basin after interacting with halite‐rich evaporites in the Triassic section before entering fractured Lower and Middle Jurassic rocks. This large‐scale meteoric invasion of the basin probably happened during early Cenozoic uplift. A similar approach was used to reveal that, in the eastern part of the basin close to the area that underwent most uplift, uppermost Jurassic and Cretaceous rocks underwent vein formation in the presence of marine connate water suggesting a closed system. Stratigraphically underlying Upper Jurassic mudstone and Lower Cretaceous sandstone, in the most uplifted part of the basin, contain veins that resulted from intermediate behaviour with input from saline meteoric water and marine connate waters. Thus, while source‐rock‐derived CO2 seems to have permeated the entire section, water movement has been more restricted. Oil‐filled inclusions in vein calcite have been found within dominant E‐W trending normal faults, suggesting that these may have facilitated oil migration.